2016
DOI: 10.1007/s10120-016-0598-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of weekly intraperitoneal versus intravenous paclitaxel therapy delivered from the day of radical surgery for gastric cancer: a preliminary safety analysis of the INPACT study, a randomized controlled trial

Abstract: Background Peritoneal carcinomatosis is common after curative resection of gastric cancer. Intraperitoneal administration of paclitaxel (PTX) is known to control ovarian peritoneal metastases. Patients and methods Patients with either linitis plastica or T4 cancer with high risk of peritoneal metastasis or recurrence but whose cancer was considered resectable were preregistered. After their cancer had been confirmed intraoperatively as resectable, the patients were randomized into either group A (PTX at 60 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 28 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…A subgroup appeared to benefit, but this would only be hypothesis generating 52, 53 . Also, perioperative intraperitoneal chemotherapy is being assessed 54, 55 . The CY-PHOENIX trial showed that intraperitoneal chemotherapy for CY-positive patients (no other site of metastasis) resulted in conversion to CY-negative in 36 patients (94.7%) and 84.2% of the 1-year OS rate 55 .…”
Section: Standard Treatment For Metastatic Patientsmentioning
confidence: 99%
“…A subgroup appeared to benefit, but this would only be hypothesis generating 52, 53 . Also, perioperative intraperitoneal chemotherapy is being assessed 54, 55 . The CY-PHOENIX trial showed that intraperitoneal chemotherapy for CY-positive patients (no other site of metastasis) resulted in conversion to CY-negative in 36 patients (94.7%) and 84.2% of the 1-year OS rate 55 .…”
Section: Standard Treatment For Metastatic Patientsmentioning
confidence: 99%
“…We previously reported on the feasibility and safety of the protocol treatment [13]. In brief, the incidence of surgical complications was similar between the two groups, except for the fact that transient bowel obstruction was observed exclusively in the IP group.…”
Section: Safetymentioning
confidence: 86%
“…Before embarking on exploring more complex treatment regimens in combination with other drugs and systemic therapy, we aimed to make a head-to-head comparison of IP vs. IV paclitaxel as a single agent for gastric cancer with high risk of peritoneal disease [12]. IP paclitaxel was found to be safe and feasible in the current multi-institutional randomized phase II trial (INPACT trial), and these results have been published [13]. Here, we report on the final analyses including survival outcomes of the trial.…”
Section: Introductionmentioning
confidence: 99%
“…This trial aimed to provide a theoretical basis for the implementation of intraperitoneal administration of PTX into various combination chemotherapy regimens in future clinical trials. In a preliminary report, Kodera et al stated that the repeated intraperitoneal administration of PTX from the day of gastrectomy was safe and feasible and that the incidence of problems associated with the indwelling catheter for intraperitoneal administration was minimal [65]. The results of an analysis of the two-year recurrence-free survival is expected in 2017.…”
Section: Clinical Outcomes For Intraperitoneal Administration Of Ptx mentioning
confidence: 99%
“…Clinical outcomes of intraperitoneal chemotherapy that utilize PTX and DTX for gastric cancer are shown in Tables 1 [52,53,[57][58][59][60][61][62][63][64][65] and 2 [50,[66][67][68][69][70][71][72]. The results of ongoing or recent clinical trials performed by the Japan Intraperitoneal Chemotherapy Study Group (JIPG) to verify the efficacy of intraperitoneal chemotherapy are also shown in Table 3 [73].…”
Section: Clinical Outcomes For Intraperitoneal Administration Of Ptx mentioning
confidence: 99%